2001
DOI: 10.1159/000049641
|View full text |Cite
|
Sign up to set email alerts
|

Social Perceptions of Male Pattern Baldness. A Review

Abstract: The paper presents a review of the empirical literature on strangers’ perceptions of male pattern baldness (androgenic alopecia). It also discusses some sociocultural aspects of hair in general, and hair loss in particular.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…A review of experimental research on the social perception of MPB (Henss, 2001) showed that male hair loss, by and large, has a negative impact on the perception of physical attractiveness ("handsome appearance") but an ambiguous effect on the perception of social attractiveness ("likeable impression"). This conflicts with the PAS prediction of a consistently negative impact on both attractiveness dimensions (Dion et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…A review of experimental research on the social perception of MPB (Henss, 2001) showed that male hair loss, by and large, has a negative impact on the perception of physical attractiveness ("handsome appearance") but an ambiguous effect on the perception of social attractiveness ("likeable impression"). This conflicts with the PAS prediction of a consistently negative impact on both attractiveness dimensions (Dion et al, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Mannes (2013) also finds that hairless scalps are associated with increased perceptions of dominance and that men with hairless scalps are perceived to be taller and stronger than they actually are. Methodologically, Henss (2001) criticizes the ecological validity of studies that rely on line drawings or schematic computer-composed faces, a problem that we do not face as we use real political leaders' faces.…”
Section: Baldnessmentioning
confidence: 99%
“…Because good scalps are a sign of health compared with the sparse or brittle hair seen during disease or starvation (Randall, 2008, p. 314), medicine has a long history of concern with baldness. For example, Hippocrates (400 BC) notes that eunuchs do not become bald (Henss, 2001), while the oldest recorded medical prescription (dating back to the Egyptians 5,000 years ago) is for treatment against baldness (Parrotto, 1961, cited in Muscarella & Cunningham, 1996). Today, we know that disposition toward balding is positively correlated with a higher ratio of DHT/testosterone (Knussmann, Christiansen, & Kannmacher, 1992), while baldness itself is associated not with total testosterone but with the amount of testosterone that is not bound to proteins in the blood (i.e., free testosterone; Demark‐Wahnefried et al., 1997).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The answer seems to be that Pliny, in the first century, saw a fox whose urine made the places on which plants would normally grow turn ‘barren and bald for a year’, thereby creating an effect rather like alopecia 1 . Next I read a review article on social perceptions of male pattern baldness 2 …”
mentioning
confidence: 99%
“…1 Next I read a review article on social perceptions of male pattern baldness. 2 The first part dealt with the effects of hair loss on those who were losing it; not surprisingly, very few of them enjoyed the process. Then came a useful summary of the many published investigations into the ways in which other people react to those who are losing their hair.…”
mentioning
confidence: 99%